IMPLEMENTASI COMPOSITE PERFORMANCE INDEX DALAM MENENTUKAN SISWA BERPRESTASI DI MA ISLAMIYAH SEI KAMAH II - Parini; Widya Amanda Susilo; William Ramdhan (Program Studi Sistem Informasi, Universitas Banten Jaya, 2025)
The selection of outstanding students at MA Islamiyah Sei Kamah II was previously conducted manually and subjectively, without a structured and transparent assessment standard. The evaluation relied solely on report card scores, disregarding other factors such as attendance, non-academic achievements, and student behavior, which could impact the objectivity of the selection process. To address this issue, this study implements a Decision Support System (DSS) based on the Composite Performance Index (CPI) method to enhance accuracy and transparency in selecting outstanding students. The CPI method integrates various assessment criteria with assigned weights, including report card scores (40%), non-academic achievements (30%), behavior (20%), and attendance (10%). The system is web-based, developed using PHP and MySQL to systematically manage student data. The implementation results indicate that the developed system effectively ranks students more objectively and accurately, ensuring a fair and accountable selection process. With this system, the school can improve the quality of student evaluations and provide more appropriate recognition for high-achieving students. Future recommendations include expanding the system’s accessibility through an Android-based application to enhance usability and efficiency in managing student data.